Volatility Transmission between Oil Prices and Stock Prices as a New Source of Instability: Lessons from the UK Experience - Robertson, John (Asian Journal of Economics and Empirical Research, 2020)
The banking industry is one of the main regulators of the economy; therefore, a possible decline in performance or risk to operations could trigger a chain of unexpected economic events. In consideration of this, this paper sought to evaluate the risk imposed by the oil and gas sector on the banking industry in the United Kingdom (UK) by evaluating the spillover effects and the exposure of the banking industry to shocks caused by changes in oil prices. In order to reach this objective, the present study evaluated the impact and effect of the volatility of bank stock prices and oil prices in four leading banks in the UK. These banks—HSBC, Royal Bank of Scotland, Lloyds Banking Group and Barclays PLC—were selected on the basis of their involvement in the oil and gas sector, and they were chosen to represent the volatility of the banking industry. The change in price of Brent crude oil was used as a representation of the volatility imposed by the oil industry. The vector autoregressive fractionally integrated moving average (VARFIMA) model was used to evaluate the impact of the volatility spillover and to evaluate the presence of co-volatility between certain parameters. The results showed volatility responses between the BSP and oil prices. The Granger causality analysis confirmed the presence of bidirectional causality between the volatility caused by oil prices and the stock prices of banks.